Study on the Influence of Work Environment on Head Nurses' Managerial Innovation and Organizational Citizenship Behaviour - Kassem, Awatef Hassan; Ahmed, Maysa Fekry (Issues and Development in Health Research Vol. 6, 2021)
Objective: In the rapid changes and competitiveness of health care organizations around the world, organizations need to recruit as well as retain talented and innovative nurses who behave like citizens, It is not easy to achieve it without suitable work environment. Work environment is the natural surroundings of the physical and emotional characteristics of a working place that the nurses devote greatest of their working times. Positive work environment is a creative, motivating, pleasurable, and well for managers, staff nurses and patients. It improves patient outcomes, nurses performance and innovation. The current study aims to investigate the role of work environment on managerial innovation and organizational citizenship behavior at Mansoura University Hospital (MUH) and Elmahala Chest Hospital (ECH). Materials and Methods: The study was conducted at Main Mansoura University Hospital (MMUH) and Elmahala Chest Hospital (ECH). The total sample was 140 nursing staff. Three tools were employed in this study, Managerial Innovation Questionnaire, Work Environment Questionnaire and Organizational Citizenship Behavior Questionnaire. Results: Total work environment at main university hospital was higher (37.1%) than Elmahala Chest Hospital (31.4%) Also Agreement of managerial innovation was higher at main university hospital than at Elmahala Chest Hospital (21.0%, 14.3%) respectively the total organizational citizenship behavior highest agreement in Elmahala Chest Hospital (48.6%) rather than Main University hospital (44.8%). Finally There is a strong positive significance relation between total work environment and both total of managerial innovation and citizenship behaviour in both setting (**p<0.01) Conclusion: There is a possibility of improving managerial innovation and organizational citizenship behaviors through improving their working environment. Recommendations: Efforts must be made to foster a healthcare environment that nurtures innovation and organizational citizenship behavior. Also involving nurses in setting goals anddecisions of organizations to develop the organizational citizenship behavior.